Pengaruh ICT Demands dan ICT Resources Terhadap Job Satisfaction Melalui Work-Family Balance Sebagai Variabel Intervening Pada Perusahaan Beauty industry di PT XYZ - Haifa Aghnia; Yohana Cahya F. Palupi Meilani (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the influence of Information and Communication Technology (ICT) Demands and ICT Resources on Job Satisfaction, with Work-Family Balance as a mediating variable, among employees in the beauty industry, particularly at PT XYZ. As digital transformation accelerates, the integration of ICT into daily work operations has significantly altered employees' work dynamics, including their work-life balance and Job Satisfaction. In this context, ICT Demands refers to the pressures and expectations caused by the use of technology, while ICT Resources represent the available support such as training, infrastructure, and access to adequate digital tools. Using a quantitative approach, data were collected from 150 active employees at PT XYZ who regularly engage with ICT in their job roles. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to assess the relationships among the variables. The findings reveal that ICT Demands has a significant negative impact on both Work-Family Balance and Job Satisfaction, whereas ICT Resources have a significant positive effect on these outcomes. Furthermore, Work-Family Balance was found to be a significant mediator in the relationships between ICT-related factors and Job Satisfaction.